Pengaruh Penggunaan Pupuk Organik Hayati terhadap Sifat Kimia Tanah di Kecamatan Pare Kabupaten Kediri - Siti Mujanah, Tjahjo Purtomo Tiuma Wiliana Susanti Panjaitan (AGROKNOW, 2014)
Abstract. This activity aims to return soil fertility level passes soil quality repair process with biological organic fertilizer use, so that increase result and agro product quality. watchfulness activity about biological organic fertilizer (POH) is done at village pelem, pare (kediri) with plants object doesnt use POH and use POH between 1 up to 7 year. soil sample taking appointeds at random and done several chemistries analysis, pregnancy poh both for still new (4 also that sufficiently long day)s (1 month). data is analyzed with anova and to detect difference delivers treatment is done test lsd in standard 5%.Â Based on research that done, got several conclusions, that is (1) biological organic fertilizer (POH) that stills new (fermentation during 4 day)s not yet give stable organic ingredient result. but such biological organic fertilizer can direct be used for organic ingredient increase in soil although the result less optimal. biological organic fertilizer best fermented during around 1 month; (2) biological organic fertilizer increasing into soil as much as 2 ton/ha to every planting will give optimal organic ingredient since gift during 7 year; (3) biological organic fertilizer use into soil will increase according to significant towards pH, P,K,Ca and Mg with KTK soil since biological organic fertilizer gift in the year first, on the contrary can demote availability SO4. Kata kunci: Pupuk Organik Hayati (POH), kimia tanah